2013
DOI: 10.1002/jsfa.6175
|View full text |Cite
|
Sign up to set email alerts
|

α‐Linalool – a marker compound of forged/synthetic sweet basil (Ocimum basilicum L.) essential oils

Abstract: The results of the chemical and statistical analyses give more pro arguments for the synthetic/forged oil hypothesis and suggest that α-linalool could be used as a marker compound of such O. basilicum oils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…According to Politeo et al, the two most important compounds in basil oil were linalool (28.6 wt%) and estragole (21.7 wt%), although present in smaller concentrations than observed in the current work. This difference is probably due to the source of the essential oil, which can significantly affect the composition of the main components, as reported by Simon and Radulović et al…”
Section: Resultssupporting
confidence: 46%
“…According to Politeo et al, the two most important compounds in basil oil were linalool (28.6 wt%) and estragole (21.7 wt%), although present in smaller concentrations than observed in the current work. This difference is probably due to the source of the essential oil, which can significantly affect the composition of the main components, as reported by Simon and Radulović et al…”
Section: Resultssupporting
confidence: 46%
“…Since then, linalool has become a dominant substance used in the fragrance, food, and cosmetic industries, and its worldwide production is about to expand in the near future (15,42). Our results demonstrated that a multistep exposure of a wild-type S. Senftenberg strain to sublethal concentrations of linalool is adequate to increase the resistance of the strain not only to linalool itself but also to the whole oily extract of basil oil and even to several antibiotics used in clinical and veterinary medicine, suggesting that the commercial use of an unspecified sublethal concentra-…”
Section: Discussionmentioning
confidence: 99%
“…One such extract (basil oil) is obtained from Ocimum basilicum L., which has widely been reviewed for its antimicrobial properties. Basil oil and each of its principal constituents-linalool, estragole, and eugenol (2, 5-10)-have largely been used in the food, sanitary, cosmetic, and perfume industries, with an estimated annual global level of production of more than 100 tons (7,(11)(12)(13)(14)(15). The industrial usage of basil oil is likely to grow steadily in the future due to its potential applications in antimicrobial technologies and the global green consumerism trend that has resulted in increasing demand for natural compounds (3,9).…”
mentioning
confidence: 99%
“…O. basilicum majorly contains about 20 compounds such as linalool, estragole, methyl eugenol, 1, 8-cineole, etc., which has been identified by GC-MS 30 . Camphor, limonene, thymol, citral, α-linalool, β-linalool, estragole, are the monoterpene's of O. basilicum.…”
Section: Phytochemical Studiesmentioning
confidence: 99%
“…The intensely purple pigment of flower is due to the presence of anthocyanins 32 . Linalool (52.42%), methyl eugenol (18.74%), 1,8-cineol (5.61%) are the major compounds in O. basilicum which are isolated by the HPLC method 30 . Myrcene, borneol and neral are the minor compounds present at 5%, 9%, 8% w/w respectively.…”
Section: Phytochemical Studiesmentioning
confidence: 99%